The influence of wages and allowances on productive working hours and business income at PT Hai Wah Talbuk Timika - Nugroho, Eko Joko; Hutajulu, Halomoan; Mollet, Ary (Global Academy of Business Studies, 2024)
Purpose: This study examines the influence of wages and allowances on productive working hours and business income at PT Hai Wah Talbuk, a medium-sized enterprise in Mimika, Papua. It identifies which compensation component—wages or allowances—most affects productivity and how productive hours impact revenue. Methodology: A quantitative approach using 2017–2024 time-series secondary data was applied. Variables included wages, allowances, productive working hours, and company income. Multiple linear regression analyzed the effect of wages and allowances on working hours, while simple linear regression assessed the impact of productive hours on income. Classical assumption tests validated the model. Results: Wages had a significant positive effect on productive working hours (p < 0.05), while allowances were positive but insignificant. Productive working hours strongly influenced business income (R² = 0.966; p < 0.01), confirming a direct link between productivity and financial performance. Conclusions: Wages significantly boost productive working hours and, in turn, company income, while allowances have a weaker effect. Productive hours are a key driver of revenue, emphasizing the role of effective wage policies. Limitations: The study focuses on one company, excluding qualitative factors like leadership or organizational culture. Contribution: Provides empirical evidence for SMEs and policymakers to prioritize monetary compensation over non-cash benefits to improve labor productivity and revenue in remote, resource-limited regions.